Epidemiology of hip fracture in Chiang Mai - Rojanasthien S. (2014)
The incidence of hip fracture varies worldwide. From 1997 to 1998, the incidence of hip fracture in Chiang Mai was 151.2 and 185.2 per 100,000 from the hospital survey and the community survey respectively. The mortality rate in hospital following hip fracture was 2.1% and the one-year mortality rate rose steadily to 37%. In addition, morbidity after hip fracture may also carry serious implications on the functional independence and quality of life. Concerning the costs for treatment, hip fracture is also a great burden for the health service in Thailand. The risk factors for hip fracture include age, medical co-morbidities, current use of antihistamine, history of fracture, alcoholic consumption, low calcium intake and lack of physical activity, whereas calcium intake and physical activity were demonstrated as important protective factors against hip fracture. Improved understanding for epidemiology of hip fracture in Thailand could enhance the effectiveness for prevention of the fracture.